(untitled) (Indonesian Journal of Agricultural Resource and Environmental Economics, 2025)
The Ministry of Agriculture of the Republic of Indonesia in collaboration with PT Asuransi Jasa Indonesia (Jasindo) has established the Cattle / Buffalo Business Insurance (AUTS / K) program since 2016. The purpose of AUTS/K is to provide protection to farmers’ businesses in the event of death and/or loss of livestock. The research was conducted from February to May 2024 in Lampung, East Java, and South Sulawesi Provinces as representative provinces throughout Indonesia. This study aims to analyze the amount of Willingness to Pay (WTP) for the premium increase and its influencing factors. Data were collected through online interviews with 67 farmers. The analysis methods used include the Contingent Valuation Method (CVM) and Maximum Likelihood Estimator (MLE). The average willingness of farmers to pay an increase in livestock insurance premiums was Rp106,250 per head per year. Factors influencing WTP include income, education, and satisfaction assessment. Kementerian Pertanian Republik Indonesia berkolaborasi dengan PT Asuransi Jasa Indonesia (Jasindo) telah membentuk program Asuransi Usaha Ternak Sapi/Kerbau (AUTS/K) sejak tahun 2016. Tujuan penyelenggaraan AUTS/K adalah memberikan perlindungan kepada usaha peternak jika terjadi kematian dan/atau kehilangan ternak. Penelitian dilaksanakan bulan Februari – Mei 2024 di Provinsi Lampung, Jawa Timur, dan Sulawesi Selatan sebagai perwakilan provinsi di seluruh Indonesia. Penelitian ini bertujuan untuk menganalisis besaran Willingness to Pay (WTP) terhadap kenaikan premi beserta faktor-faktor yang memengaruhinya. Pengumpulan data dilakukan dengan wawancara secara online kepada 67 peternak. Metode analisis yang digunakan meliputi Contingent Valuation Method (CVM) dan Maximum Likelihood Estimator (MLE). Rataan kesanggupan peternak dalam membayar kenaikan premi asuransi ternak senilai Rp106.250,00 per ekor per tahun. Adapun faktor yang memengaruhi WTP meliputi pendapatan, pendidikan, dan penilaian kepuasan peternak.